2020
DOI: 10.3390/ijms21144952
|View full text |Cite
|
Sign up to set email alerts
|

From Inflammation to Cutaneous Repair: Topical Application of Lupeol Improves Skin Wound Healing in Rats by Modulating the Cytokine Levels, NF-κB, Ki-67, Growth Factor Expression, and Distribution of Collagen Fibers

Abstract: Skin wound healing is a highly complex event that involves different mediators at the cellular and molecular level. Lupeol has been reported to possess different biological activities, such as anti-inflammatory, antioxidant, antidiabetic, and in vitro wound healing properties, which motivated us to proceed with in vivo studies. We aimed to investigate the wound healing effect of lupeol-based cream for 3, 7, and 14 days. Wound excisions were induced on the thoraco-lumbar region of rats and topically treated imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 45 publications
5
17
0
1
Order By: Relevance
“…The pro-inflammatory markers IL-1b and IL-6 values were comparable among all the studied groups, similar to the previously published articles [ 94 , 95 ]. At the same time, tumor necrosis factor α (TNF-α) significantly increased in the negative control group compared to the intact group ( p < 0.0001).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The pro-inflammatory markers IL-1b and IL-6 values were comparable among all the studied groups, similar to the previously published articles [ 94 , 95 ]. At the same time, tumor necrosis factor α (TNF-α) significantly increased in the negative control group compared to the intact group ( p < 0.0001).…”
Section: Resultssupporting
confidence: 91%
“…Furthermore, TNF-α regulates blood coagulation, contributes to oxidative stress at sites of inflammation, and indirectly induces fever. The data conforms with Gushiken and Periera, where TNF-α decreased after two weeks of treatment in skin wound tissue compared to the negative control [94,95].…”
Section: Role Of Pro-and Anti-inflammatory Markers In Wound Healingsupporting
confidence: 90%
“…Regarding the effect of lupeol, Pereira-Bessera et al observed that in vitro, lupeol has a beneficial effect on wound healing due to the fact that it has anti-inflammatory properties [33]. Subsequently, the same team of researchers proved the protective and repairing effect of lupeol in wounds, this time using a murine model [34].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several studies direct the use of LUP towards the treatment of skin injuries. For instance, Beserra’s research group shows that lupeol exerts beneficial effects in cutaneous repair both in vitro by promoting wound healing in human keratinocytes and fibroblasts, and in vivo by regulating collagen distribution and the expression of several markers (i.e., cytokines, NF-κB, Ki-67, growth factor) [ 27 , 28 ]. Recent research focused on exploring the efficiency of LUP in the treatment of various cancers (i.e., lung, liver, pancreas, head, and neck), offering valuable insight into the molecular mechanisms underlying its anti-tumor properties [ 29 , 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%